High NK cell counts at day 90 predict improved survival in event-free patients after T-cell depleted allogeneic stem cell transplantation - Pešić, Andrej; Bešević, Nevena; Kröger, Nicolaus; Stanisavljević, Dejana; Kraguljac Kurtović, Nada; Bukumirić, Zoran; Kecman, Natalija; Lemajić, Nikola; Smiljanić, Mihailo; Suvajdžić Vuković, Nada; Bogdanović, Andrija; Vidović, Ana; et al. (Frontiers in Immunology, 2025)
IntroductionImmune reconstitution (IR) after allogeneic stem cell transplantation has been highlighted as pivotal in achieving favorable long-term outcomes by influencing the rates of infection, graft versus host disease (GvHD) and relapse. However, data on the impact of different lymphocyte subsets influencing outcomes is conflicting. Furthermore, the importance of immune reconstitution parameters in patients previously not experiencing major post-transplant complications is lacking.MethodsWe evaluated the clinical impact of day 90 NK cell, CD4+ T-cell, CD8+ T-cell, B-cell, and NKT cell counts on transplant outcomes by performing a landmark analysis in event-free patients. Lymphocyte subset counts were obtained from 70 patients undergoing in vivo T-cell depleted allogeneic transplantation from 2018 to 2024. Patients eligible for the study experienced no acute GvHD, poor graft function, graft failure, or relapse in the first three months after transplantation-prior to obtaining IR data. We associated lymphocyte subset counts to overall survival (OS), non-relapse mortality (NRM), cumulative incidence of relapse (RI), and secondary graft failure/poor graft function.ResultsHigh NK cell counts on day 90 (>178/μL) were associated with improved OS (P=0.039) and lower rates of NRM (1-year cumulative incidence of 5.7% versus 31.4%, HR 0.16, 95% CI 0.04-0.69, P=0.014). A protective effect on RI was not found. We found no patient, disease or transplant-related variables to be significantly associated with day 90 NK cell counts.ConclusionThe results suggest that high NK cell counts on day 90 after T-cell depleted allogeneic transplantation independently protect from NRM and improve OS in patients without prior major post-transplant complications.